New normal educational leadership and management of geographically challenged school administrators in the Division of Capiz - Ferry Rafunzel Manuba; Ryan Estillomo (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The pandemic has ramshackle the already technologically debilitated condition of education extenuating the need for forces, knowledge and talents of teachers and parents toward achieving better education. With this, the study determined the educational leadership and management challenges of school administrators in the Division of Capiz which may serve as basis in creating primers for supplementary material of the Learning Continuity Plan. Specifically, it covered the   changes, challenges, managerial skills and leadership styles of school administrators. In-depth unstructured Interviews using open-ended questions were used to gather the data from six (6) selected school administrators in the Division of Capiz. The data gathered were analyzed through the qualitative data analysis procedures presented by Powell and Renner (2003). The themes identified were based on the changes encountered by the school administrators in the new normal setting. These were on organizational management strategies, personnel monitoring, instructional delivery system, and health management protocols. The identified themes based on the challenges experienced by school administrators as to the implementation of the new normal setting of education were poor internet connection, transportation fare hike, threats on health and safety, parents’ involvement, scarcity of school resources and adjustments.